Age and employment status as dominant factors in medication adherence among hypertensive patients - Abadi, Moh Fairuz; Prasetya, Didik; Pratama, Putu Teguh Surya (Poltekkes Kemenkes Bandung, 2026)
Background: Hypertension is a common chronic condition that requires consistent medication adherence to prevent complications. Despite various control programs, adherence remains influenced by sociodemographic factors. Objective: This study aimed to examine the association between sociodemographic characteristics, national health insurance enrollment (JKN), smoking habits, and medication adherence among hypertensive patients. Methods: This cross-sectional study was conducted at the Mengwi Public Health Center, Badung Regency, Bali Province. The study population included 611 adult hypertensive patients, and 239 respondents were selected using random sampling. The dependent variable was medication adherence, while the independent variables were age, gender, marital status, education, employment status, household position, JKN membership, and smoking habits. Data were analyzed using the Chi-square test to assess associations. Results: The results showed that among 239 participants, 82.8% adhered to their medication. Age was significantly associated with adherence (p = 0.008), and regression analysis (p = 0.901; OR = 1.001; 95% CI: 0.980–1.023) indicated a small effect but a pattern where older and middle-aged patients were more compliant than younger adults. Employment status was also significantly related to adherence (p = 0.039), with regression results (p = 0.039; OR = 3.125; 95% CI: 1.061–9.206), showing a positive association. Other variables, including gender, marital status, education, household position, JKN membership, and smoking habits, were not significantly associated. Conclusion: Age and employment status significantly influenced medication adherence among hypertensive patients. These findings emphasize the importance of age- and occupation-based interventions, such as adherence education for younger patients and time management strategies for employed individuals.